Analisis Faktor-Faktor yang Mempengaruhi Status Gizi Balita - Wahyudi Wahyudi Istiono, Heni Suryadi, Muhammad Haris, Irnizarifka, Andre Damardana Tahi (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: The first two years in life are critical period in which rapid growth and development occured. Nutritional status of children under five years old is influenced by several factors, such as social, economic, cultural, health, environmental, and demographic factor. The World Health Organization reported that protein- energy malnutrition (PEM) prevalence in Indonesia was high. It was estimated that 27.5% of children under five years old were experienced from moderate malnutrition, while 8.5% of them were severely malnourished.Objective: This study is aimed to determine nutritional status of children under five years old as well as to identify the correlation between risk factors and the nutritional status on the area of Dukuh Madigondo, Sidoharjo Village, Samigaluh Subdistrict, and the District of Kulonprogo.Methods: The design of this study was observational with cross sectional study to identify 15 risk factors associated with nutritional status in children under five years old. Subjects were 48 children under five years old which assessed with research questionnaires. Correlation among variables was then analyzed using Kruskal Walis One Way Anova and Pearson Chi Square Test.Result: The nutritional status of fourty four children under five years old were good, while two of the children were below standard and the remaining two were bad in nutritional status. Pearson Chi Square analysis has showed no significant correlation between nutritional status and sickness frequency, familial characteristics, expenditure, environmental hygiene sanitation, health care access, mother act, mother behavior, along with mother knowledge factor.Conclusion: There was no significant correlation found among 15 risk factors towards nutritional status of children under five years old in Dukuh Madigondo, Sidoharjo Village, Samigaluh Subdistrict, District of Kulonprogo.Keywords: nutritional status, children under five years old, sex, sickness frequency, familial characteristics, expenditure level, environmental hygiene sanitation, health care access, mother act, mother behavior, mother knowledge